ENHANCING CENTRAL RESOURCES AND SOCIAL CAPITAL TO INCREASE CUSTOMER LOYALTY IN THE CONTEXT OF SERVICES AT ENGLISH CENTERS - Nguyen Tran Cam Linh; Duong Quynh Nga; Phan Thi Ngoc Tam; Vuong Minh Khoa (Economics & Education, 2019)
The purpose of the study was to examine the impact of social capital (including structural social capital, relational social capital, and cognitive social capital) and central resources (including programs, reputation, and the competence of frontline staff) on student satisfaction and loyalty. The primary data collection technique that is questionnaire was used for the purpose of analyzing the data. It was distributed to 310 respondents from 68 English centers. The data collected was analyzed through a Structural equation modeling – SEM. The findings of the study revealed that four statistically significant factors affecting customer loyalty are the interpersonal competence of frontline staff, teacher competence, learning facilities and cognitive social capital. Among these ones, cognitive social capital directly influences loyalty, and the other three indirectly affect customer loyalty through customer satisfaction. Factors that do not affect loyalty include programs, reputation, structural social capital, relational social capital.